2019
DOI: 10.2147/ndt.s212328
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparative diagnostic accuracy of ACE-III and MoCA for detecting mild cognitive impairment</p>

Abstract: ObjectiveThe aim of this study was to validate the reliability of the Chinese version of Addenbrooke’s Cognitive Examination III (ACE-III) for detecting mild cognitive impairment. Furthermore, the present study compares the diagnostic accuracy of ACE-III with that of Montreal Cognitive Assessment (MoCA).MethodsOne hundred and twenty patients with MCI and 136 healthy controls were included in the study. All patients were evaluated by the Chinese version of ACE-III, MoCA and MMSE.ResultsSubjects in the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The Mini‐Mental State Examination (MMSE) and MoCA are widespread and concise screening tools for the assessment of cognitive impairment that has a significant impact on the evaluation of age‐related cognitive decline 20 . Recently, the MoCA has been developed to detect mild cognitive impairment with a score range 0–30 in China and other countries 21–23 . In addition, MoCA can address orientation, drawing figures, processing speed, naming objects, memory, recall, attention, vigilance, repetition, verbal fluency, and abstraction 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The Mini‐Mental State Examination (MMSE) and MoCA are widespread and concise screening tools for the assessment of cognitive impairment that has a significant impact on the evaluation of age‐related cognitive decline 20 . Recently, the MoCA has been developed to detect mild cognitive impairment with a score range 0–30 in China and other countries 21–23 . In addition, MoCA can address orientation, drawing figures, processing speed, naming objects, memory, recall, attention, vigilance, repetition, verbal fluency, and abstraction 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors recruited 120 patients with MCI, and 136 healthy controls, and showed a positive correlation between ACE-III results and other common cognitive assessment methods (Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE)). They also showed ACE-III to have higher diagnostic accuracy in detecting MCI when compared with the MMSE 1. We would like to thank the authors for highlighting the success of the Chinese version of ACE-III in diagnosing MCI and would like to offer some comments regarding their study.…”
Section: Dear Editormentioning
confidence: 98%
“…One review also states age to be a consideration, with people over 75 scoring less in comparison with younger people 4. Wang et al show significant differences in age and education level in their study, with patients in the MCI group being, on average, 7.5 years older and 4.0 years more educated than their control counterparts 1. We agree with the authors that any further studies about the Chinese version of ACE-III should take education level into consideration, to avoid any bias due to patient population.…”
Section: Dear Editormentioning
confidence: 99%
“…Twelve patients were also evaluated through the Adenbrooke's Cognitive Examination Revised (ACE-R). The ACE-R provides evaluation of six cognitive domains (orientation, attention, memory, verbal fluency, language, and visual ability) and is useful to detect mild cognitive impairment [29,30].…”
Section: Subjects and Clinical Evaluationmentioning
confidence: 99%